Remote ischemic preconditioning ameliorates anthracycline-induced cardiotoxicity and preserves mitochondrial integrity - Galán Arriola, Carlos (2021)
Aims: Anthracycline-induced cardiotoxicity (AIC) is a serious adverse effect among cancer patients. A central mechanism of AIC is irreversible mitochondrial damage. Despite major efforts, there are currently no effective therapies able to prevent AIC. Methods and results: Forty Large-White pigs were included. In Study 1, 20 pigs were randomized 1:1 to remote ischaemic preconditioning (RIPC, 3 cycles of 5 min leg ischaemia followed by 5 min reperfusion) or no pretreatment. RIPC was performed immediately before each intracoronary doxorubicin injections (0.45 mg/kg) given at Weeks 0, 2, 4, 6, and 8. A group of 10 pigs with no exposure to doxorubicin served as healthy controls. Pigs underwent serial cardiac magnetic resonance (CMR) exams at baseline and at Weeks 6, 8, 12, and 16, being sacrifice after that. In Study 2, 10 new pigs received 3 doxorubicin injections (with/out preceding RIPC) and were sacrificed at week 6. In Study 1, left ventricular ejection fraction (LVEF) depression was blunted animals receiving RIPC before doxorubicin (RIPC-Doxo), which had a significantly higher LVEF at Week 16 than doxorubicin treated pigs that received no pretreatment (Untreated-Doxo) (41.5 ± 9.1% vs. 32.5 ± 8.7%, P = 0.04). It was mainly due to conserved regional contractile function. In Study 2, transmission electron microscopy (TEM) at Week 6 showed fragmented mitochondria with severe morphological abnormalities in Untreated-Doxo pigs, together with upregulation of fission and autophagy proteins. At the end of the 16-week Study 1 protocol, TEM revealed overt mitochondrial fragmentation with structural fragmentation in Untreated-Doxo pigs, whereas interstitial fibrosis was less severe in RIPC+Doxo pigs. Conclusion: In a translatable large-animal model of AIC, RIPC applied immediately before each doxorubicin injection resulted in preserved cardiac contractility with significantly higher long-term LVEF and less cardiac fibrosis. RIPC prevented mitochondrial fragmentation and dysregulated autophagy from AIC early stages. RIPC is a promising intervention for testing in clinical trials in AIC.